Keberadaan Tari Antan Bagonto Di Kecamatan Pulau Punjung Kabupaten Dharmasraya - Eliza Permata Sary; Fuji Astuti (FBS Universitas Negeri Padang, 2022)
This research aims to reveal and describe the Existence of the Antan Bagonto Dance in the Punjung Island District of Dharmasraya Regency. This type of research is a type of qualitative research with descriptive methods. The data collection techniques used are literature studies, observations, interviews and documentation. Data collection techniques are carried out by employing Library Studies, Observations, and Interviews. The steps of data analysis are data collection, analyzing data and making conclusions. The results of the study showed the Existence of Antan Bagonto Dance in Punjung Island Subdistrict as seen from the periodization per year. The study looked at 5 periodizations ranging from 1957-1982, 1983-2014, in 2015, 2016-2018 and 2019. The causative factors of the ups and downs of Antan Bagonto Dance are the entry of the development of science and technology, Band, and also pandemics.